THE EFFECT OF BIOFERTILIZER CONCENTRATION ON GROWTH AND YIELD OF THREE LOCAL SUMEDANG VARIETIES OF RICE (ORYZA SATIVA L.) IN DRYLAND: PENGARUH KONSENTRASI PUPUK HAYATI TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS PADI SAWAH LOKAL SUMEDANG (ORYZA SATIVA L.) DI LAHAN KERING - Rosalina Fitria; Lia Amalia; Kovertina Rakhmi Indriana (ROCE : Jurnal Pertanian Terapan, 2024)
Biofertilizer is a product that contains living substances consisting of microorganisms that are useful for plants. The role of microorganisms contained in biofertilizers is to function as a fixer and nutrient provider for plants. Local rice varieties varieties have been adapted and have location-specific characteristics. Drylands have the potential to increase agricultural production. This research aims to study the interaction between the concentration of biofertilizer and varieties on the growth and yield of local Sumedang varieties of rice planted in dry land. The experimental method used a Factorial Randomized Group Design. The first factor is the concentration of biological fertilizer consisting of three levels, namely p1 = 0 ml L-1 of water p2 = 3 ml L-1 of water, p3 = 6 ml L-1 of water while the second factor is the local Sumedang varieties of rice consisting of three types of varieties, such as v1 = Gemah, v2 = Gede Wangi, V3 = Trisakti. The results showed that the concentration of biofertilizer 6 ml L-1showed the highest production of varietas Trisakti with 573 gram per square.